The best of times. (Economist, 2018)
The article looks at advantages and disadvantages provide by financial inclusion to the financial system. Fintechs are regarded as reformists in the financial system. The use of application programme interfaces (APIs) is recognized for allowing services on platforms of banks. Some challenges related to financial inclusion are discussed, including concerns on digital security and competition.